The Challenges of Copyright Protection in the Digital Age: Between Innovation and Piracy - Aicha Azdina Adly Fesya; Asfrianda Mulia NST; Akbar Rayfades; Mu’ammar Rafsanjany; Awal Diwangga (Jurnal Sahabat ISNU SU, 2025)
The development of digital technology has brought significant changes in the patterns of creation, distribution, and consumption of creative works. While the digital era encourages innovation and ease of access to intellectual works, it also increases copyright infringement practices such as digital piracy. This situation poses serious challenges for the copyright legal protection system, particularly in maintaining a balance between protecting the interests of creators and the public interest. This study aims to analyze the challenges of copyright protection in the digital era and examine legal remedies that can be taken to address piracy practices. The research method used is normative juridical research with a statutory and conceptual approach, through a review of copyright-related laws and regulations and relevant legal literature. The research stages include collecting primary and secondary legal materials, normative analysis, and drawing deductive conclusions. The results indicate that weak law enforcement, low public legal awareness, and technological developments that are faster than regulations are the main factors contributing to the rise of digital piracy. Therefore, strengthening regulations, increasing public legal literacy, and synergy between the government, creative industry players, and digital platforms are needed to create an effective and equitable copyright protection system in the digital era.